Replication data for: Improving association studies and genomic predictions for climbing beans with data from bush bean populations - Keller, Beat; Ariza-Suárez, Daniel; Portilla Benavides, Ana Elisabeth; Buendia, Hector Fabio; Aparicio, Johan Steven; Amongi, Winnyfred; Mbiu, Julius; Msolla, Susan N.; Miklas, Phillip N.; Porch, Timothy G.; Burridge, James D.; Mukankusi, Clare; et al. (2022)
Genomic predictions for climbing beans were established. The climbing bean panel (VEC) was phenotypically and genotypically characterized. To improve association studies and predictions, contrasting bush type bean data, i.e., publicly available data as well as data from new field trials, were added to the data set.